Impact of Cloud Manufacturing on Delivery Delays within the Coffee Industry Supply Chain - De la Cruz Montalvo, Gracielita Ivón (2025)
Abstract — This applied research aimed to evaluate the impact of implementing a Cloud Manufacturing system on delivery delays within the supply chain of Café DLópez, a coffee processing and distribution company in Junín, Peru. A pre-experimental design with a single group was used, comparing delivery performance over two six-month periods before and after the implementation of a collaborative system developed in Google Sheets. The diagnostic phase identified key weaknesses in traceability, coordination, and technological integration, which were addressed through the deployment of a cloud-based management solution. The system enabled real-time order tracking, inventory visibility, and delivery scheduling across departments. Statistical analysis using the paired samples t-test revealed a significant reduction in average delivery delays, from 2.7 to 0.8 days (p = 0.028). These findings confirm that lightweight, accessible platforms like Google Sheets can serve as effective tools for digitalizing logistics processes in small agro-industrial enterprises, contributing to greater efficiency and customer satisfaction.